2019
DOI: 10.3389/fneur.2019.01323
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Upper Limb Motor Function in Ethiopian Acquired Brain Injured Patients Using a Low-Cost Wearable Sensor

Abstract: Acquired brain injuries place a significant burden on sub-Saharan African rehabilitation clinicians and health care facilities. While wearable sensors have the potential to alleviate these issues, many are beyond the financial capabilities of the majority of African persons and clinics. To bridge this gap, we have developed a low-cost wrist-worn sensor (the outREACH sensor) capable of accurately measuring upper limb movement kinematics. In this study we evaluated the extent to which the outREACH sensor is sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Aligning with previous studies ( Hughes et al, 2019a ; Hughes et al, 2019b ), we have shown promising validity for movement kinematics detected using single IMU-based systems. Although increasing the number of IMUs would allow for the calculation of kinematics across multiple joints, it would also increase the cost of the system as well as its usability as a decentralized rehabilitation tool.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Aligning with previous studies ( Hughes et al, 2019a ; Hughes et al, 2019b ), we have shown promising validity for movement kinematics detected using single IMU-based systems. Although increasing the number of IMUs would allow for the calculation of kinematics across multiple joints, it would also increase the cost of the system as well as its usability as a decentralized rehabilitation tool.…”
Section: Discussionsupporting
confidence: 87%
“…Another enabling technology are inertial measurement units (IMUs) that exhibit great potential as a low-cost, portable means to evaluate and monitor patient progress during decentralized rehabilitation protocols ( Parrington et al, 2021 ). IMUs have been shown to accurately measure motor function and provide information regarding the different motor components that contribute to task performance, (e.g., movement accuracy, efficiency, precision, smoothness) ( Hughes et al, 2019a ; Schwarz et al, 2019 ), with kinematic variables obtained by IMU-based system correlating with standard clinical assessments ( Hughes et al, 2019b ; Oubre et al, 2020 ; Chen et al, 2021 ). For example, Hughes et al (2019a) , Hughes et al (2019b) developed a low-cost IMU-based wearable sensor specifically designed for medically underserved populations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such technology is capable of providing detailed information regarding upper extremity function evaluation and delivering personalized interventions. According to the previous literature, kinematic assessment is usually performed using arm-supported robots or optical-camera systems, based on fixed laboratory environments or expensive equipment that leads to several disadvantages [11][12][13]. From the technical perspective, robotic instruments are unable to capture the entire spectrum of UE motor impairment due to their mechanical structure [14].…”
Section: Introductionmentioning
confidence: 99%